Pontos periódicos quase elípticos em sistemas dinâmicos conservativos - Andre Ribeiro de Resende Alves (2012)
Our objective is analize some generic properties of conservative and symplectic dynamical systems. We will focus our atention in two results we consider particularly relevant: Pixton's theorem, which proves the existence of a residual set of diffeomorphisms in R2 for which every hyperbolical periodic point has transverse homoclinic intersection; and a theorem by Newhouse, that proves the existence of a subset B Diffr!(M) such that if f 2 B then every quasi-elliptic periodic point of f is the limit of transverse homoclinic points off.